Longest Very Late Stent Thrombosis of Second Generation Drug Eluting Stent - Almohammadi, Ramzi A. (Cardiology and Cardiovascular Medicine, 2024)
Stent thrombosis (ST) is a catastrophic complication of coronary stenting, presenting as sudden death or nonfatal myocardial infarction (MI) in almost all cases. ST was considered a time-limited event, with occurrences reported only during the first 30 days after stenting and confirmation of most cases within the first week(1). We are reporting a case in our institution that sustained anterior ST segment elevation myocardial infarction (STEMI) 7 years after initial implantation of Xience Prime second generation DES in the mid segment of LAD. The patient was taken to cardiac catheterization lab and found to have thrombotic occlusion of previously placed Xience Prime DES 7 years ago in mid segment of LAD; TIMI flow was zero distal to the thrombotic occlusion. To our knowledge, this is the longest reported intervening period between second generation Xience Prime DES insertion and the development of an acute coronary event secondary to very late stent thrombosis (VLST).